Statistical Challenges in “Big Data” Human Neuroimaging - Smith, Stephen M.; Nichols, Thomas E. (Neuron (Cambridge, Mass.), 2018)
Smith and Nichols discuss “big data” human neuroimaging studies, with very large subject numbers and amounts of data. These studies provide great opportunities for making new discoveries about the brain but raise many new analytical challenges and interpretational risks. Smith and Nichols discuss “big data” human neuroimaging studies, with very large subject numbers and amounts of data. These studies provide great opportunities for making new discoveries about the brain but raise many new analytical challenges and interpretational risks.